Assessment of awareness about diabetic retinopathy among Diabetics in primary health care centre of Al-Kharj, Saudi Arabia - Othman Jarallah Al Jarallah (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: Diabetes mellitus (DM) is a metabolic condition characterized by chronically elevated blood glucose levels. It damages various organs and tissues of the body, including the eyes, nerves, heart, kidney and blood vessels. Diabetic retinopathy (DR) can impact 24 percent of diabetes patients with the condition for 10–15 years. This study was carried out with an objective to assess the level of public awareness and create an understanding of a possible complication like diabetic retinopathy among diabetic patients.Methods: This cross sectional study was conducted among Saudi nationals in Riyadh Province, Saudi Arabia. The data was collected based on a self- constructed questionnaire. The study involved a total of 103 confirmed cases of type 2 DM. Saudi DM patients who visited PCC between 15-80 years of age were included in the study. Patients who were not Saudi, had congenital eye disease, had experienced prior eye trauma, were known cases of or being treated for other eye diseases like cataract or glaucoma, and had a history of cognitive impairment were excluded from the study. Results: the results indicated that 79.6% (n=82) of diabetics were aware that diabetic retinopathy was a possible complication of diabetes. Out of these, 16.5% (n=17) extracted this information from the media while 46.6% (n=48) relied on medics. More than half (57.3%, n=59) reported that Diabetes could cause blindness whereas 56.9% (n=58) reported DM could affect eye without affecting the vision and need treatment within that time. About two-thirds (62.1%, n=64) had consulted a doctor earlier and half of them (46.6%, n=68) visited the doctor due to some symptom. Besides, the majority (68.0%, n=70) of the patients had no idea about various treatment modalities for diabetic retinopathy.Conclusion: this study showed that majority (79.6%) of diabetics were aware of DR being a possible complication to DM and only 46.6% got this awareness from specialist doctors while 16.5% extracted this information from the media.